Evaluation of hemodialysis vascular access involving multidisciplinary integration: Perspective from Latin America and Peru - Castillo Velarde, Edwin; Ruiz-Peñafiel, José A.; Alfaro Ita, Sheyla; Vachharajani, Tushar J. (Frontiers in Nephrology, 2023)
The perspective of vascular access care in patients with end-stage renal disease has migrated from nephrology-centered or vascular surgery-centered to multidisciplinary focused patient-centered. This new perspective should be not only theoretical but also with practical utility. A non-multidisciplinary focus can contribute to the low prevalence of arteriovenous fistula (AVF) in the population. Latin-América has multiple health systems and the coordination on vascular access is heterogeneous. In Perú, there is a high prevalence of central venous catheter use with its associated complications, like stenosis, thrombosis, infection, and recurrent hospitalizations in the context of fragmented care. However, in the last few years, there is an effort to integrate the communication between vascular surgery, interventional radiology, and nephrology to improve vascular access care. In this review, we analyze the availability of care, the intervention, and the future directions from the experience of both perspectives.